BIOLOGICAL AND CHEMICAL ANALYSIS EDUCATION AND TRAINING PROGRAM FOR THE COMMUNITY FOR AWARENESS OF HERBAL PRODUCT SAFETY in CANDIREJO VILLAGE - Fahdi, Firdaus; Sembiring, Bungamari; Purba, Bahtera Bindavid; Sari, Herviani (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
The utilization of herbal products has gained popularity due to their perceived safety compared to synthetic drugs. However, a lack of education on the safety and analytical methods of herbal products remains a significant challenge for communities. This program aims to enhance the awareness and skills of Candirejo Village residents in ensuring the safety of herbal products through biological and chemical analysis training. Methods such as Thin Layer Chromatography (TLC) and UV-Vis spectrophotometry were introduced to participants to detect active compounds and hazardous substances. The results indicate increased understanding of herbal product safety, practical skills in simple analysis, and local economic empowerment through the development of safe herbal products. The program is expected to be sustainable with the establishment of community-based working groups, contributing to the supervision and innovation of herbal products at the local level. Through educational and hands-on approaches, this initiative positively impacts health, the economy, and community awareness regarding the safety of herbal products.